THE EFFECT OF ORDINARY CRUCIAL SKILL TO IMPROVE UNIVERSITY STUDENTS' ACADEMIC READING SKILLS - Masrul, Masrul; Erliana, Santi (Jurnal Pendidikan Bahasa Inggris Proficiency, 2024)
Previous surveys on college academic reading often utilized questionnaires and lacked in-depth analysis to assess students' reading skills. This present study involving 80 students of Universitas Pahlawan assessed students’ academic reading skills using Correlation Test, Manova Test, and Duncan Test. In addition to examine the importance of these skills, this study also identified the need to have adequate academic reading skills. The gap between the pre-test and post-test signified the significant effects on reading skill, analysis and evaluation, reading strategies and efficiency, and influential factors. However, comprehension skills, linguistic discourse, and knowledge did not have a significant effect. Furthermore, this study also discusses the implications for researchers and for the practices of the course.